Tax Aggressive Practices in Indonesia: Transfer Pricing, Capital Intensity Ratio, and Institutional Ownership - Erma Wulan Sari; Rihan Mustafa Zahri; Mareta Putri Hapsari; Abelita Adinda Putri; Vikha Hersa Agustin (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to analyze the effect of Transfer Pricing, Capital Intensity Ratio, Institutional Ownership on the practice of Tax Aggressiveness. The dependent variable used in this study is Tax Aggressiveness while the independent variables are Transfer Pricing, Capital Intensity Ratio, Institutional Ownership. The population in this study are Real and Estate companies listed on the IDX for the 2018-2021 period. The sampling technique used in this study was purposive sampling so that a total sample of 48 companies was obtained with a total data of 192. The data analysis technique in this study used Multiple Linear Regression Analysis with SPSS 25. The results of the show that Transfer Pricing has an effect on tax aggressiveness, companies that carry out transaction with related parties have a tendency to practice tax aggressiveness. The Capital Intensity Ratio affects the practice of tax aggressiveness, the Capital Intensity Ratio can show a company’s efficiency in using its assets so that it can be used as a method of minimizing the tax burden that must be paid by the company. Institutional Ownership does not affect the practice of tax aggressiveness, Institutional Ownership has an important role in the company to monitor the performance of managers, so that managers do not dare to act aggressively to practice tax aggressiveness. Keywords: Tax Aggressiveness, Transfer Pricing, Capital Intensity Ratio, and Institutional Ownership.